Strength-plasticity synergistic enhancement of dispersion strengthened copper by interaction of nano-Al2O3 and Cr particles - Hao Song; Shaolin Li; Xiuhua Guo; Kexing Song; Song Liu; Keke Qi (Materials & Design)
To further regulate the coordinated matching of mechanical properties and plastic deformation ability of Al2O3/Cu composites. In this paper, Al2O3/Cu-Cr composites with different Cr contents were prepared by replacing some Al2O3 particles with Cr using a deformation heat treatment process, and the effects of Cr contents on the microstructure, electrical conductivity, and mechanical properties of Al2O3/Cu-Cr composites were investigated with a focus on the contribution of the composite strengthening mechanism. The results show that with the increase of Cr content and the decrease of Al2O3 content, the strength of the composites gradually decreases, and the plasticity and electrical conductivity are enhanced. Among them, the elongation of 1.1 Al2O3/Cu-0.3Cr composites was enhanced from 10% to 15% while the strength was not considerably reduced. The addition of Cr promotes grain growth and dynamic recrystallization, whereas Al2O3 particles enhance the aging precipitation response of Cr particles. The results of strength mechanism calculations show that the tensile strength of Al2O3/Cu-Cr composites mainly consists of Orowan strengthening caused by Al2O3 particles and dislocation strengthening in cold rolled deformation, while the dislocation strengthening is weakened at higher Cr content.